KONTRIBUSI LITERASI DIGITAL DAN INTERAKSI BELAJAR ANTAR SISWA TERHADAP KETERAMPILAN MEMECAHKAN MASALAH PEMBELAJARAN IPAS - Dewi Nurjanah; Syamsul Hadi; Ahmad Yusuf Sobri (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2024)
The improvement of skills relevant to the 21st century focuses on students' ability to explore the surrounding environment. For this it is necessary to train students' problem-solving skills from the natural environment as well as human behavior in public life that require contributions in their achievements. The aim of the study was to determine the contribution of digital literacy and learning interaction between students to IPAS (IPA and IPS) problem-solving skills of 4th grade primary school students in Waru Sidoarjo District. The research uses a quantitative approach of survey methods. The primary data used was obtained directly from the field. Data source 181 respondents across five sampled schools after reduction. The result was that both free variables contributed positively and significantly to the IPAS problem-solving skills of grade IV elementary students. The standard values of the coefficients in each variable showed different values, namely digital literacy of 0.187, while the learning interaction between students was 0.177. The results showed that the digital literacy variable was the more dominant variable